Actualization of Manhaj al Fikr Aswaja to Develop Critical Thinking Skills of Students at MAN 1 Tuban - Atalafairus Iklil Warsanda (Konsultan Jurnal Ilmiah Indonesia, 2025)
The digital era and globalization demand that the younger generation have critical thinking skills that are intellectually intelligent as well as morally and socially wise. This study aims to analyze the understanding, actualization, and influence of the Ahlussunnah wal Jamaah (Aswaja) method on the critical thinking of students at MAN 1 Tuban. The method used is descriptive qualitative with intrinsic case studies, involving observation, interviews, and documentation. The results show that students have a good understanding of Aswaja values, such as tawassuth (moderation), tasamuh (tolerance), tawazun (balance), ta'adul (justice), and naqli-aqli balance. These values ​​are actualized through learning, class discussions, book studies, extracurricular activities, and madrasah culture, including the practice of tabayyun. Actualization of the Aswaja method improves students' ability to select information, construct logical arguments, appreciate different perspectives, and solve problems objectively. The study confirmed Aswaja as an effective methodological framework for developing moderate, tolerant, just, and rational students.